2022
DOI: 10.1108/ecam-01-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain technology in construction organizations: risk assessment using trapezoidal fuzzy ordinal priority approach

Abstract: PurposeIn the digital transformation era, the construction industry is not immune to unintended consequences and disruptions of distributed ledger technologies like blockchain. At the micro-level, construction organizations need an in-depth understanding of blockchain risks to take proactive strategies for being on the safe side. This study seeks to answer “What are the risks associated with blockchain technology from the firm-level perspective? And how can this disruptive technology overshadow the business ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The Ordinal Priority Approach (OPA) is firstly introduced by Ataei et al ( 2020). After that, the benefits of their method have emerged in numerous studies such as the assessment of construction sub-contractors (Mahmoudi & Javed, 2022), suppliers for healthcare center assessment (Quartey-Papafio, Islam, & Dehaghani, 2021), agriculture sector (Islam, 2021), robot selection (Abdel-Basset, Mohamed, Abdel-Monem, & Elfattah, 2022), risk assessment (Sadeghi, Mahmoudi, & Deng, 2022), postpandemic strategies (Le & Nhieu, 2022), and planning strategies prioritization (Pamucar, Deveci, Gokasar, Martínez, & Köppen, 2022).…”
Section: Studies Applied the Ordinal Priority Approachmentioning
confidence: 99%
“…The Ordinal Priority Approach (OPA) is firstly introduced by Ataei et al ( 2020). After that, the benefits of their method have emerged in numerous studies such as the assessment of construction sub-contractors (Mahmoudi & Javed, 2022), suppliers for healthcare center assessment (Quartey-Papafio, Islam, & Dehaghani, 2021), agriculture sector (Islam, 2021), robot selection (Abdel-Basset, Mohamed, Abdel-Monem, & Elfattah, 2022), risk assessment (Sadeghi, Mahmoudi, & Deng, 2022), postpandemic strategies (Le & Nhieu, 2022), and planning strategies prioritization (Pamucar, Deveci, Gokasar, Martínez, & Köppen, 2022).…”
Section: Studies Applied the Ordinal Priority Approachmentioning
confidence: 99%
“…Xu et al [6] found that a lack of information technology infrastructure and legal and regulatory uncertainty are the most prominent barriers toward blockchain technology adoption in the architectural engineering and construction (AEC) industry. Similarly, Sadeghi et al [9] showed that organizational communication and information are exposed to higher risk using blockchain technology through case studies, and developed a conceptual blockchain technology risk management framework. Furthermore, Badi et al [22] assessed the TOE framework using a deductive questionnaire-based approach.…”
Section: Conceptual Background a Potential Factors Affecting Blockcha...mentioning
confidence: 99%
“…The low innovation, discontinuity, and complex construction processes of the engineering-construction industry may lead to differences in technical, organizational, and environmental factors [8] that determine whether organizations will adopt blockchain technology. Furthermore, studies on blockchain adoption are still in the fledging stage [6,9], and prior studies have primarily focused on conceptual research [10] or employed the traditional symmetric approach [11]. Blockchain technology adoption is a complex process with complex contextual conditions [12], resulting in managerial decisions based on symbiotic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Han and Wang [ 8 ] argue that the core step of intelligent construction is to visualize the construction project by collecting data to assist the relevant parties in decision-making. Deng et al [ 9 ] propose blockchain technology as one of the fundamental components of intelligent transformation in the construction industry, and it has the potential to address issues related to procurement and supply chain, big data, and data storage [ 10 ]. As can be seen, intelligent construction is the combination of advanced technologies such as BIM, IoT, blockchain, and 4D visualisation technology with each other to achieve integrated project management, which promotes collaboration between relevant parties and the efficient use of resources and energy throughout the construction process and promotes the sustainable development of the entire construction industry.…”
Section: Literature Reviewmentioning
confidence: 99%